Resultado de los estudios regionales de introducción y adaptación de especies y variedades pascícolas en zonas semiáridas del SW español (Pastos, 1977)
Results from a series of triáis conducced in S.W. Spain between 1972-1976 using different species and varieties of grasses and legumes indicated the advantages from fertilizer applications in all the áreas studied with the exceptions of "La Serena" and "Palomas-Hornachos". Soil deph was also a major factor determining the success of pasture establishment and subsequently persistence and production. The Australian subclover cultivare used in these triáis did not generally persist adequately. It is tberefore concluded that there is a need to select "local" ecotypes of this species and of others species that are more adapted to the environmental conditions of the zone. More information is also required on the environmental factors, managerial practicas and agro- nomic characteristics that contribute to persistence of annual legumes. It is believed that persistence is the major determinant of success in pasture improvement involving the use of annual legumes; with perennial grasses in S.W. Spain, establishment appears to be major determinant. 222